Empowerment of Coastal Community's Social and Economic in Bima Regency, Indonesia - Yasin, Haerun; Haeril, Haeril (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
The purpose of this study was to determine the socio-economic empowerment strategy of the coastal community of Bima Regency. This study used the descriptive qualitative method. The location of this research is the Department of Tourism, the Department of Marine Affairs and Fisheries, and the Department of the Environment of Bima Regency. The results of the study indicate that in the socio-economic empowerment of coastal communities, the District Government of Bima implements a community empowerment program in controlling and controlling marine fisheries resources by forming Pokmaswas. In addition, empowerment is also carried out through the coastal community economic empowerment program (PEMP) in realizing a fishing community that has the motivation, skills, and broad insight and is able to understand in a group forum through programs to improve and develop, process and quality fishery products, develop fishing and fishing business sectors. cultivation and fishery product processing business. Also assistance for the Empowerment of the People's Salt Business (PUGAR). Empowerment is also carried out from the tourism sector, especially in supporting the SAKOSA priority program through the development of the Creative Economy (Ekraf) in boosting the economy of coastal communities. In addition, there is also a Tourism Awareness Group (Pokdarwis) for coastal communities formed to create partnerships in the development, arrangement, maintenance, and promotion of tourism in Bima Regency.